ChemInform Abstract: Variation of Structural Motifs in Lanthanoid Hydroxo Clusters by Ligand Modification. Issue 17 (4th April 2013) - Andrews, Philip C.; Gee, William J.; Junk, Peter C.; Massi, Massimiliano
Abstract Review: 70 refs.